2024
DOI: 10.1101/2024.02.26.582140
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The spatiotemporal dynamics of bottom-up and top-down processing during at-a-glance reading

Nigel Flower,
Liina Pylkkänen

Abstract: Like all domains of cognition, language processing is affected by top-down knowledge. Classic evidence for this is missing blatant errors in the signal. In sentence comprehension, one instance of this is failing to notice word order errors, such as transposed words in the middle of a sentence: you that read wrong (Mirault et al., 2018). Our brains seem to fix such errors, since they are incompatible with our grammatical knowledge. But how do our brains do this? Following behavioral work on inner transpositions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…This lack of a clear effect of wh -subjects may be due to their linear position in the RPVP stimulus. All 3 languages position the subject at the beginning of the clause, thus they are likely to fall outside of the foveal center, and may therefore not be processed as accurately or quickly, which is observed in other RPVP tasks (Snell & Grainger 2019; Dunagan et al 2024; Flower & Pylkkänen 2024). Moreover, the forms of the wh - and non- wh subject in all languages and conditions are orthographically short ( wh -subjects: who , کس kis-ne , 谁 shéi ; non wh -subjects: she / he ; اسنے us-ne ; 她 / 他 tā ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This lack of a clear effect of wh -subjects may be due to their linear position in the RPVP stimulus. All 3 languages position the subject at the beginning of the clause, thus they are likely to fall outside of the foveal center, and may therefore not be processed as accurately or quickly, which is observed in other RPVP tasks (Snell & Grainger 2019; Dunagan et al 2024; Flower & Pylkkänen 2024). Moreover, the forms of the wh - and non- wh subject in all languages and conditions are orthographically short ( wh -subjects: who , کس kis-ne , 谁 shéi ; non wh -subjects: she / he ; اسنے us-ne ; 她 / 他 tā ).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms supporting reading entire sentences rapidly presented are still under debate (e.g., Wen et al 2019; Dufau et al 2024; Fallon & Pylkkänen 2024; Flower & Pylkkänen 2024; Dunagan et al 2024). Nonetheless, we showed that readers can extract key grammatical information from sentences displayed in 200ms in English, Urdu, and Mandarin Chinese.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations